Educational Supervisors' Strategies in Improving ECCE Principals' Managerial Competence in the Digital Era: A Case Study - Nandang Rukanda; Sri Nurhayati (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study investigates the strategies educational supervisors employ to enhance the managerial competence of Early Childhood Care and Education (ECCE) principals in the digital era. A qualitative case study was conducted in Bandung City, with 7 educational supervisors as informants. Data were gathered through semi-structured interviews, observations, and document analysis, and thematically analyzed to discern patterns in strategy use, strategy evaluation, and challenges in the digital era. Key findings reveal supervisors' strategies are diverse and situational, including regular training, mentoring, coaching, collaborations, and supervision, all adapted to the digital context. Success is evaluated through data-driven indicators and evaluation processes, highlighting the role of monitoring, needs identification, socialization, and communication. Challenges faced include motivational deficits, resistance to change, and resource constraints. This research contributes to a deeper understanding of supervisory strategies in the digital era, emphasizing the importance of adaptable, context-sensitive approaches in enhancing ECCE principals' managerial competence. It underscores the role of digital fluency in leadership development and offers insights into effective strategies and prevalent challenges within early childhood education.